Manual therapy and exercise effects on inflammatory cytokines: a narrative overview - Cook, Chad E.; Keter, Damian; Cade, William Todd; Winkelstein, Beth A.; Reed, William R. (Frontiers in Rehabilitation Sciences, 2024)
Background Matching disease and treatment mechanisms is a goal of the Precision Medicine Initiative. Pro- and anti-inflammatory cytokines (e.g., Tumor Necrosis Factor-alpha, Transforming Growth Factor-beta, and Interleukin-2, 10, and 12) have gained a significant amount of interest in their potential role in persistent pain for musculoskeletal (MSK) conditions. Manual therapy (MT) and exercise are two guideline-recommended approaches for treating MSK conditions. The objective of this narrative overview was to investigate of the effects of MT and exercise on pro- and anti-inflammatory cytokines and determine the factors that lead to variability in results. Methods Two reviewers evaluated the direction and variabilities of MT and exercise literature. A red, yellow, and green light scoring system was used to define consistencies. Results Consistencies in responses were seen with acute and chronic exercise and both pro- and anti-inflammatory cytokines. Chronic exercise is associated with a consistent shift towards a more anti-inflammatory cytokine profile (Transforming Growth Factor-beta, and Interleukin-2 and 13, whereas acute bouts of intense exercise can transiently increase pro-inflammatory cytokine levels. The influence of MT on cytokines was less commonly studied and yielded more variable results. Conclusion Variability in findings is likely related to the subject and their baseline condition or disease, when measurement occurs, and the exercise intensity, duration, and an individual's overall health and fitness.